Ecotopic infection of cattle with Fasciola gigantica: parasitological and pathological studies - AL-Kubaisee, R. Y.; Alwan, M. J.; AL- Kaisee, B. (The Iraqi Journal of Veterinary Medicine, 1999)
Out of 1250 bovine fasciolliasis. 10 cattle were found to have lung fascioliasis, one cow had abomasal fascioliasis and another one wih renal fascioliasis. The recovered flukes were identified as immature spec imens of Fassciola gigantica .Gross and histopathology of the lesions were studied. The occurrence of Fasciola gigantica in kideny and abomasum was recorded for the first time : Introduction Infection with Fasciola gigantica is an important cause of disease and economic loss in domestic animals in many parts of the world. Among the effects attributed 10 flucke infection are loss of condition , reduced meat and milk production reduced fertility and rendering of livers unsuitable for human consumpiior. . Severe infection may cause death either directly or indirecily by inzitiating or aggravating bacterial infection (1). One of the reasons making F.gigantica more pathogenic ihan F.hepatica is frequent ecotopic occurence of F.gigantica in most of the domestic animal species (1,2,3).Ectopic ovine F.gigantica infection was reported in spleen, lung, heart, diphragm and portal vein, in additional the liver (4,5). In cattle F.hepatica_ could only produce lesions in the liver but F.gigantica extended its pathogenic effects to the lung tissue (3,6). The aim of this study is to elucidate the occurence of F.gigantica in organs other than the liver with parasitological and pathological investigation.